The effect of dentifrice ingredients on enamel erosion prevention and repair. (15th February 2021) - Fowler, Christabel E.; Creeth, Jonathan E.; Paul, Alan J.; Carson, Clare; Tadesse, Gebremedhin; Brown, Alan
Abstract : Fluoride is a key dentifrice ingredient for mitigating dental erosion and promoting remineralisation in tooth enamel. A dentifrice formulation (NaF/CL ‐ where C = Copolymer, L = Lactate), optimised for fluoride delivery, containing sodium fluoride, polyvinylmethylether–maleic anhydride (PVM/MA) copolymer and lactate ion at controlled pH of 6.2 is compared with six commercial dentifrices from European and US regulatory regions. The in vitro study utilised white light interferometry (WLI) and dynamic secondary ion mass spectrometry (DSIMS) to assess dental erosion resistance and remineralisation potential of the dentifrices. For WLI, polished enamel samples were immersed in dentifrice slurry (1:3 wt./wt. in artificial saliva, 2 min), brushed, washed in deionised water, acid challenged (1% citric acid, pH 3.8, 5 min), washed and air dried. Surface roughness and bulk tissue loss were measured. DSIMS samples for fluoride uptake were acid challenged (1% citric acid, pH 3.8, 5 min), rinsed, immersed in dentifrice slurry (1:3 wt./wt. in artificial saliva, 2 min), washed and air dried. DSIMS samples for 44 Ca uptake were prepared similarly but with 44 Ca‐doped artificial saliva. The NaF/CL dentifrice provided highest protection against dental erosion, with highest fluoride and 44 Ca uptake in all treatment groups ( n = 5 per group). Dentifrices containing other fluoride salts and/or ingredients known to inhibit fluoride uptake (e.g., polyphosphates, sodium lauryl sulfate), performed significantly worse.